" Self- conscious in modern liberal political thought (John Locke, Immanuel Kant as a model) " - Walid Mosaher Hamad; Mahdi , Abeer Siham (Tikrit Journal For Political Science, 2022)
self -conscious And knowledge has emerged as important in modern liberal political thought and came in order to call for the importance of awareness in the essence of the individual, as it was mentioned by most of the leading critics, most notably John Locke and Emmanuel Kant. And there are no innate ideas in it, but at the same time it confirms the existence of an innate power in the mind and not ideas that can transform simple ideas into a vehicle that produces ideas, knowledge and awareness, through which the mind begins in a negative way to receive these external impressions in the mind and contemplate them in the form of simple ideas, either practical Acquisition of self -conscious in Kant was formed through his attempt to combine rationalists and empiricists, as he worked to link experience with the mind through the presence of pre-experienced subjective categories, perceptions and conditions that exist in the mind, which can be called innate ideas found in the pure mind and others that come from the senses by their interaction with external things. self -conscious according to Kant is a process that takes place entirely within the self on a substance that comes from without, which is the sensory data of phenomena, which constitute the external substance of things in themselves. The two images of space and time and the categories of understanding are self-perceptions that exist in the mind in an a priori way, and then he started applying them to what I consider to be the appearance of things.